Narrow-bandwidth sensing of high-frequency fields with continuous dynamical decoupling. Issue 1 (December 2017) - Stark, Alexander; Aharon, Nati; Unden, Thomas; Louzon, Daniel; Huck, Alexander; Retzker, Alex; Andersen, Ulrik; Jelezko, Fedor
Abstract State-of-the-art methods for sensing weak AC fields are only efficient in the low frequency domain (<10 MHz). The inefficiency of sensing high-frequency signals is due to the lack of ability to use dynamical decoupling. In this paper we show that dynamical decoupling can be incorporated into high-frequency sensing schemes and by this we demonstrate that the high sensitivity achieved for low frequency can be extended to the whole spectrum. While our scheme is general and suitable to a variety of atomic and solid-state systems, we experimentally demonstrate it with the nitrogen-vacancy center in diamond. For a diamond with natural abundance of13 C, we achieve coherence times up to 1.43 ms resulting in a smallest detectable magnetic field strength of 4 nT at 1.6 GHz. Attributed to the inherent nature of our scheme, we observe an additional increase in coherence time due to the signal itself. State-of-the-art methods for sensing weak AC fields are only efficient in the low frequency domain. Here, Stark et al. demonstrate a sensing scheme that is capable of probing high frequencies through continuous dynamical coupling by applying it to a nitrogen-vacancy centre in diamond.